The ratio of chloride to bicarbonate is a predictor of advanced metabolic acidosis in CKD stages G4 and G5 - Justyna Korus; Maciej Gołębiowski; Jakub Stojanowski; Maciej Szymczak; Marcelina Żabińska; Dorota Bartoszek; Katarzyna Kościelska-Kasprzak; Mirosław Banasik; Milena Ściskalska; Mariusz Kusztal; Tomasz Gołębiowski (Scientific Reports)
Abstract Metabolic acidosis is a common disorder in patients with chronic kidney disease (CKD). As eGFR decreases, a reciprocal decrease in bicarbonate (HCO3 −) and an increase in chloride (Cl−) concentration is observed. The aim of this study is to determine whether the Cl−/HCO3 − ratio can be used to predict metabolic acidosis with pH decline. A total of 115 patients (age 63 ± 17 years), with CKD stage G4 or G5 were enrolled in this cross-sectional study. The arterial (A) and venous (V) blood samples were taken during AV fistula creation and evaluated in a point of care testing analyzer. The ratio of arterial Cl− and HCO3 − concentration were calculated. According to mean arterial pH (pH-A) the group was divided into group with pH-A ≤ 7.33 and with pH-A > 7.33. The group with pH-A ≤ 7.33 showed significantly lower HCO3 −, and higher Cl−, Cl−/HCO3 −-ratio than group with pH-A > 7.33. Cl−/HCO3 −-A ratio negatively correlated with pH (r=-0.77,p < 0.01). The discriminative power of Cl−/HCO3 −-A ratio for predicting pH-A ≤ 7.33 was 0.917 ([CI] = 0.87–0.97,p < 0.01) which provided 87% sensitivity and 84% specificity. The best cut-off was 6.22(mmol/l)/(mmol/l). In conclusion, a Cl−/HCO3 − ratio higher than 6.22(mmol/l)/(mmol/l) may be used as predictor of advanced metabolic acidosis in CKD stages G4 and G5.